Deconstructing “de/colonised knowledge” in South Africa: the case of radical academic history under apartheid (1960-1991) - Martinerie, Camille (African Studies, 2023)
This thesis explores the inherent complexities and contradictions embedded in the radical turn in South African historiography with regards to the decolonisation of the discipline of history in South African universities under apartheid from 1960 to 1991. By choosing to deconstruct radical history in a white liberal university, the study seeks to further demonstrate the limits of intellectual decolonisation and its underlying assumptions in the academic field during apartheid. It interrogates radical history as a form of academic resistance and leads a reflection on the political role of the intellectual in the context of the anti-apartheid struggle, asking more broadly: to what extent can radical academic history be considered “de/colonised knowledge”? Building on the links between ideology and curriculum, this study aimed to measure the coloniality of history using history examination questions as tools to investigate the methodological, theoretical and ideological assumptions of historians. Theoretically, the study relied on the role of the historian as a recontextualising agent of disciplinary knowledge taught and examined within a historically white higher education institution to study its concomitant underlying historiographical silences at the time. Methodologically, it deployed quantitative and qualitative research methods, using interviews and semi-structured questionnaires with a targeted cohort of authentic interlocutors to triangulate the discursive analysis of institutionalised “de/colonised” historical knowledge. This interdisciplinary study was thus inscribed in a critical deconstructionist approach to knowledge which contributed to a finer conceptual and empirical understanding of the coloniality of history as a discipline and its reproduction in the South African higher education context. The study hopes (1) to contribute to understanding the nuanced intersections between the history of intellectual colonisation and decolonisation and how these tensions impacted on history education in the apartheid university, (2) to provide an original interdisciplinary mixed method of analysis of institutionalised “de/colonised knowledge”, and (3) to contribute new critical insights into blind spots in South African radical historiography in higher education during the period 1960 to 1991, which could shed light on the various understandings of the imperative for decolonisation today in the discipline.